A method for evaluating cold tolerance in rice during reproductive growth stages under natural low-temperature conditions in tropical highlands in Kenya. (1st October 2020) - Samejima, Hiroaki; Kikuta, Mayumi; Katura, Keisuke; Menge, Daniel; Gichuhi, Emily; Wainaina, Cornelius; Kimani, John; Inukai, Yoshiaki; Yamauchi, Akira; Makihara, Daigo
ABSTRACT: Cold tolerance of New Rice for Africa (NERICA) and their parent varieties was evaluated under natural air temperature conditions of Kenyan tropical highlands using the multiple-sown field evaluation method. Rice varieties were cultivated 10 times to expose them to a shift in temperature during 20-day periods before heading (critical period), measuring the average daily mean temperature during the critical period (Tmean ) for each variety and filled grain ratio, which was used as an indicator of cold tolerance. Tmean of each variety was low in 6 out of 10 experiments. In the remaining four high-temperature experiments, there were no significant varietal differences in filled grain ratio. In the six low-temperature experiments, all varieties experienced 20.1−21.5°C Tmean . After comparison under virtually the same cold stress, NERICA 1, 3, 4, 7−10, 12, 17, 18, and WAB 56–104 were judged as cold-tolerant; NERICA 2, 5, 11, 13, and 14, and WAB 56–50 and 181–18 were moderately tolerant, and NERICA 6, 15, and 16 were cold-susceptible varieties. These evaluations generally corresponded with previous experimental results under temperature-controlled environments, showing the practicality of multiple-sown field cold tolerance evaluation in Kenya. It also indicated that NERICA varieties, which recorded different levels of cold tolerance and whose average number of days to heading in all experiments were 66−78, are suitable as a set of standard check varieties in this region to evaluate cold tolerance of rice varieties with this range of days to heading. Graphical Abstract: uf0001